2012
DOI: 10.1111/j.1601-183x.2012.00810.x
|View full text |Cite
|
Sign up to set email alerts
|

The propensity for consuming ethanol in Drosophila requires rutabaga adenylyl cyclase expression within mushroom body neurons

Abstract: Alcohol activates reward systems through an unknown mechanism, in some cases leading to alcohol abuse and dependence. Herein, we utilized a two-choice Capillary Feeding assay to address the neural and molecular basis for ethanol self-administration in Drosophila melanogaster. Wild-type Drosophila demonstrates a significant preference for food containing between 5 and 15% ethanol. Preferred ethanol self-administration does not appear to be due to caloric advantage, nor due to perceptual biases, suggesting a hed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 47 publications
0
56
0
Order By: Relevance
“…Flies given the choice between consuming food supplemented with ethanol versus control food gradually shift their preference toward the alcoholic choice over several days (Devineni and Heberlein, 2009). Interestingly, this shift is dependent on cAMP signaling (Xu et al, 2012). Since ethanol is thought to interact with reward circuitry in the brain (Kaun et al, 2011;ShohatOphir et al, 2012), it is tempting to speculate that caloric sugar consumption and ethanol consumption activate similar circuits that ultimately impinge on feeding preference.…”
Section: Discussionmentioning
confidence: 99%
“…Flies given the choice between consuming food supplemented with ethanol versus control food gradually shift their preference toward the alcoholic choice over several days (Devineni and Heberlein, 2009). Interestingly, this shift is dependent on cAMP signaling (Xu et al, 2012). Since ethanol is thought to interact with reward circuitry in the brain (Kaun et al, 2011;ShohatOphir et al, 2012), it is tempting to speculate that caloric sugar consumption and ethanol consumption activate similar circuits that ultimately impinge on feeding preference.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the present study, where butterflies were free to feed by themselves over several hours, we did not detect positive effects of ethanol on feeding latency and duration. Experimental biases, such as the very high ethanol concentration and the absence of yeasts in the feeding solution mimicking over-ripe fruit, may explain this lack of preference (Becher et al, 2012;Mazeh et al, 2008;Xu et al, 2012). However, previous studies examining the feeding response of B. anynana butterflies in relation to ethanol concentration found that the strongest response occurred when butterflies were exposed to even higher ethanol concentrations (10%) than in the present study, and that butterflies do not alter their feeding response in relation to the presence of yeasts in their food (Dierks and Fischer, 2008;Kehl and Fischer, 2012).…”
Section: Discussion Effects Of Fruit Ripening Stage In the Absence Ofmentioning
confidence: 99%
“…The mushroom bodies are required for ethanol preference and reward (Kaun et al, 2011;Xu et al, 2012;Ojelade et al, 2015). We asked whether the role of Sir2 may extend to these other forms of ethanol behavioral plasticity.…”
Section: Sir2 Is Required For Ethanol Preference and Rewardmentioning
confidence: 99%